GSK-3β and memory formation - Takashima, Akihiko (Frontiers in Molecular Neuroscience, 2012)
In Alzheimer’s disease (AD), tau hyperphosphorylation and neurofibrillary tangle (NFT) formation are strongly associated with dementia, a characteristic and early feature of this disease. Glycogen synthase kinase 3β (GSK-3β) is a pivotal kinase in both the normal and pathological phosphorylation of tau. In the diseased state, hyperphosphorylated tau is deposited in NFTs, the formation of which, drive the disease process. GSK-3β which is also involved in long-term depression induction, interacts with tau to inhibit synaptic long-term potentiation. Strong lines of evidence suggest that the activation of GSK-3β is responsible for the memory deficits seen in both advanced age and AD. In this review, we will focus on the role of GSK-3β in brain function, particularly in memory maintenance. We will examine human and mouse studies which suggest a role for GSK-3β in memory maintenance and the eventual development of memory deficits.